Aparat Hukum dan Pembenaran Kekerasan - Rusli Muhammad (Unisia, 2006)
The law apparatus for instance police, attorney and judge (jurist) are not only as an important pillar in state but also become an element in the criminal court system. The running well system of formal procedure, but sometimes faces the critical condition that implies to conduct violence either individually or collectively that direct to hard and soft violence. The violence action that conducted by law apparatus can not separate from and closed relation to their professional experiences, the principles of inquisitoir, crime model control and formal decision either national or international.